2022
DOI: 10.9789/2175-5361.rpcfo.v14.11014
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and factors associated with dyslipidemia among people with type 2 Diabetes Mellitus / Frequência e fatores associados à dislipidemia entre pessoas com diabetes mellitus tipo 2

Abstract: Objetivo: avaliar a frequência e os fatores associados à dislipidemia em pessoas com Diabetes Mellitus Tipo 2. Método: estudo transversal, desenvolvido com 45 pessoas diagnosticadas com diabetes e acompanhadas por uma Unidade Básica de Saúde. Foram investigadas variáveis sociodemográficas, relacionadas ao estilo de vida e referentes à análise do perfil lipídico. Resultados: a prevalência de dislipidemia foi de 82,2%, significativamente associada ao sexo feminino (p=0,005), ao tabagismo (p=0,002) e ao sedentari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
4
0
4
Order By: Relevance
“…15 A higher prevalence of MS in women was observed in other studies. 4,9,16,17 It is noteworthy that more than half of the sample in the present study was composed of women. Furthermore, it is known that this number increases Pearson's *x 2 ; MW: minimum wage R$998.00; DM2: type 2 diabetes mellitus; SAH: hypertension; PR: prevalence ratio.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…15 A higher prevalence of MS in women was observed in other studies. 4,9,16,17 It is noteworthy that more than half of the sample in the present study was composed of women. Furthermore, it is known that this number increases Pearson's *x 2 ; MW: minimum wage R$998.00; DM2: type 2 diabetes mellitus; SAH: hypertension; PR: prevalence ratio.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, 57.8% of the participants had elevated triglycerides, a lipid abnormality more commonly observed in individuals with DM2. 4 Triglyceride plasma levels are higher in the elderly than in younger individuals, which may be attributed to the delay in postprandial triglyceride metabolism. Therefore, it is observed that aging is associated with increased triglycerides and visceral fat, which together increase the risk of MS. 24 From this perspective, a study found a prevalence of 27.1% of hypertriglyceridemic waistlines in the elderly in Bahia, associated with female gender, sedentary lifestyle and overweight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ademais, a dislipidemia sempre se mostra se elevada nos pacientes diabéticos. Por sua vez a associação da ocorrência de dislipidemia nas variáveis como o sexo feminino, hábitos de tabagismo e sedentarismo chama a atenção para a necessidade de melhores condutas para essa população (NETO et al, 2022).…”
Section: Hipertrigliceridemia Isoladaunclassified